EXERCISE PREVENTS AGE-RELATED MEMORY DECLINE: THE ROLE OF NEUROTROPHIC FACTORS - Rivarti, Arina Windri; Herawati, Lilik; Hidayati, Hanik Badriyah (MNJ (Malang Neurology Journal), 2020)
Increasing aging population causes an increased prevalence of neurodegenerative diseases such as dementia that is associated with memory decline. Developing strategies for the prevention and therapy of age-related dementia is important to reduce the burden of treatment costs. Physical exercise is known to prevent cognitive decline and improve cognitive abilities. Physical exercise with moderate intensity for at least 150 minutes/week or 30 minutes/day for 5 days can reduce the incidence of degenerative diseases in the elderly. Thus, physical exercise appears as a simple, inexpensive, and affordable non-pharmacological therapy for most people. The processes of neurogenesis and neuronal survival involve the role of neurotrophic factors including BDNF, IGF-1 and VEGF, which are the three main neurotrophic factors that are known to increase after exercise. Many publications discuss about these neurotrophic factors, but their mechanism of signals and changes related to aging and exercise have not been completely studied. The purpose of this review is to discuss the mechanism of signals and changes of neurotrophic factors (focuses on BDNF, IGF-1, and VEGF) related to aging and exercise.